Optimising energy efficiency and ecological ‎footprint of off-season cucumber production agro-ecosystem upon different farm levels (Case of central Iran) - Bardia Bayat; Mohammad Hossein Ansari; Marjan Diyanat; Ali Mohammadi ‎Torkashvand (Horticultural Science, 2023)
The present study aimed to use a non-parametric data envelopment analysis (DEA) to estimate the energy efficiency and greenhouse gas (GHG) emissions in off-season cucumber-producing greenhouses in different farm level management systems in Iran. Data were collected using a questionnaire completed by 83 cucumber producers through face-to-face interviews. The results showed that the energy use rate was 75.1%, 82.6%, and 86.2% in small (0.5-0.9 ha), medium (0.9-2 ha), and large farms (≥ 2 ha), respectively. In all the farm levels, the greatest energy use shares belonged to electricity, chemical fertilisers, and human labour, respectively. The results of the DEA revealed that the technical, pure technical, and scale efficiencies of the large farms were 87.3%, 92.8%, and 97.1%, respectively, which were higher compared to other farm level management systems. The ratio of energy savings was estimated at 5.62% and 2.97% for small and large farms, respectively. The results also showed that electricity, chemical fertilisers, and diesel fuel were the most responsible for the GHG emissions. By optimising the energy use, pollution per one/ha one of off-season cucumbers can be mitigated by 1 614.5 and 1 315.0 kg of CO2/ha in small and large greenhouses; indicating more attention is required in managing the energy inputs in small-sized agro-ecosystems, especially for electricity.